P91 High prevalence of vitamin d deficiency amongst patients with copd in the north east. highlighting a deficiency and need for improved assessment. (15th November 2017) - Tedd, H; Conroy, K; Mitchell, A; Shanshal, Y; Curtis, H
Abstract : Background: Vitamin D plays a key role in osteoporosis and also contributes to sarcopenia, muscle weakness, fatigue and depression. Patients with COPD are likely to be at higher risk of Vitamin D deficiency due to reduced mobility especially outdoors, with previous studies in the London area demonstrating prevalence rates around 60%. 1 However, within our population group in the North East of England, little is known about the prevalence of Vitamin D deficiency. Aims: To identify the prevalence of serum 25-hydroxyvitamin D (25(OH)-D) deficiency in patients admitted with an acute exacerbation of COPD. Method: We identified 50 patients admitted with an exacerbation of COPD. Data on demographics and prescription of vitamin D supplementation was recorded. 25(OH)-D titres were measured. Results: 50 patients included, mean age 73.6 years (age range 45–95 years). 44% of patients were prescribed vitamin D supplementation (95% of supplementation was in the form of combined calcium and vitamin D). Overall 62% of patients were found to have low 25(OH)-D titres. Of those not taking vitamin D supplementation, only 14% of patient had sufficient 25(OH)-D titres (≥50 nmol/L). 11% were 25(OH)-D insufficient (30–50 nmol/L), 57% were 25(OH)-D deficient (8–30 nmol/L) and 18% were profoundly deficient (<8 nmol/L). Of those patients taking vitamin D supplementation, 68% were found to have sufficient 25(OH)-D titres, whilst 32% still had inadequate 25(OH)-D highlighting potential issues with compliance or insufficient replacement. Conclusions: We have demonstrated a very high prevalence of vitamin D deficiency amongst our patients with COPD, with 86% of our patients having inadequate vitamin D titres who were not on vitamin D supplementation. This is leading them to increased exposure to the risks of vitamin D deficiency, including the impact on bone health in at already 'at-risk' population. In response to this, locally we are now measuring 25(OH)-D titres routinely on patients with COPD and prescribing vitamin D supplementation when indicated, forming part of our new multisystem, comprehensive, holistic assessment of COPD patients. Reference: Joliffe, et al. Prevalence, determinants and clinical correlates of Vitamin D deficiency in patients with chronic obstructive pulmonary disease in London, UK., 2017. J Steroid Biochem Mol Biochem.